نسبة مساھمة بعض القدرات البدنیة في سرعة ودقة أداء مھارة الأرسال بأنواعھ للاعبي الكرة الطائرة - حسين سبهان صخي (physical education and sport sciences college for women/ Baghdad University, 2014)
The skill of serving in volleyball is considered one of the most important skills because it has the ability to gain points and it require players with high levels of physical, motor, mental and skill abilities. The importance of the study lies in identifying the percentage of some physical contribution on the speed and accuracy of performing serving in all its types. In addition to that, it is important for coaches to identify the percentage of physical abilities contribution to identify the weaknesses and strengths in players during serving. The subjects were (16) Iraqi national volleyball league players of the season 2012 - 2013. Four of the subjects were excluded because they formed the pilot study. After identifying the skill and physical tests, the researchers performed the pilot study on Sunday and Monday 10 - 11/12/2012. The researcher concluded non - significant correlation between the physical abilities under study and speed and accuracy of floater serving from standing position in volleyball. They also concluded non - significant correlation between the physical abilities under study and speed and accuracy of floater serving from jumping position in volleyball except in throwing the medicine ball. Finally they concluded non - significant correlation between the physical abilities understudy and speed and accuracy of spiking. At the end, the researcher recommended the necessity of giving coaches enough time in training sessions for training special physical abilities to develop the speed and accuracy of serving types in volleyball.